ESTIMATION OF PINEAPPLE PRODUCTION IN MANIPUR - A STATISTICAL APPROACH - CHANGAMAYUM GIRIJA DEVI* and S. LOIDANG DEVI, (The Journal of Research ANGRAU, 2022)
The main objective of this paper was to compare the compound growth rate model, exponentialsmoothing model and ARIMA model on pineapple production in Manipur. Time series secondary datawas utilized for this analysis. From the study, it was recorded that the value of R2 for the compoundgrowth rate model, exponential smoothing model and autoregressive integrated moving averagemodel of production, suggested that out of the total variation 83.2%, 75.4%, and 85.2%, respectivelywas explained by the independent variable on the pineapple production of Manipur. In 2020 pineappleproduction in Manipur was 166483 MT and in the years 2021, 2022, 2023, 2024 and 2025 it could be160403 MT, 181650 MT, 175174 MT, 177148 MT, 176546 MT, respectively based on the fitted ARIMA(1,1,2) model, in which the production fluctuates which might be due to the fluctuation in the pastyears’ data of production.